Motorbike madness: embracing sustainable two-wheeled mobility / Muhammad Izzat Irfan Mustaffa and Dr. Nurulhusna Qamaruz Zaman - Mustaffa, Muhammad Izzat Irfan; Qamaruz Zaman, Nurulhusna (College of Built Environment, 2023)
The phenomenal motorbike dominance seen in Hanoi today developed after Vietnam embarked on the market reforms known as doi moi in 1986.